Crioimersão pós-exercício: desfechos sobre variáveis biológicas, clínicas e metabólicas a partir de diferentes temperaturas e tempos de aplicação - Albuquerque, Maíra Campos de [UNESP] (2013)
Background: Given the need to obtain optimal levels of recovery uses various strategies in the field. Among them, it is used frequently cold water immersion (CWI). However, notice is also gaps in knowledge to define the real effects of these modalities recovery under specific conditions. Objective: To analyze and compare the effects of CWI during recovery after strenuous exercise, using different time and temperature on biological variables, clinical and metabolic. Materials and Methods: 105 male individuals between 18 and 30 years were divided into five groups: a control (GC) and four recoveries (G1, G2, G3 and G4). The volunteers were subjected to exhaustion protocol which consisted of a jumping program (10 sets of 10 jumps with a minute of rest between sets) and the Wingate test. Immediately after the exhaustion protocol, volunteers were directed to a tank with water and ice, which were immersed up to the height of the anterior superior iliac spine to the recovery procedure (G1: 5 ' 9 ± 1 ° C; G2: 5 ' to 14 ± 1 º C; G3: 15' to 9 ± 1 ° C; G4: 15 ' to 14 ± 1 ° C)...